Rigorous assessment of CO2 electroreduction products in a flow cell. Issue 8 (26th July 2021) - Niu, Zhuang-Zhuang; Chi, Li-Ping; Liu, Ren; Chen, Zhi; Gao, Min-Rui
Abstract : Four overlooked measurement pitfalls during CO2 reduction reaction (CO2 RR) in flow cells are identified. A modified flow-cell system has been proposed, permitting the establishment of benchmarks by which CO2 RR products can be accurately assessed. Abstract : Electrochemical conversion of carbon dioxide (CO2 ) into valuable carbon-based chemicals provides a route to store renewable electricity and close the carbon loop. In comparison to the conventional "H-cells", the flow-cell reactors enable CO2 reduction reaction (CO2 RR) operating at much higher current densities via mitigating the mass-transport limitation issue. However, the lack of a standard testing methodology has led to inaccurate detection of CO2 RR products and thus unfair performance comparisons. Herein, we identified several commonly overlooked aspects in terms of product measurements during CO2 electrolysis in flow cells, which could cause a considerable misestimation even up to a ratio of 45% in certain scenarios. Systematic experiments suggest a modified flow-cell testing system that permits the establishment of benchmarks by which CO2 RR products can be accurately assessed. Our study, for the first time, offers a rigorous protocol towards the accurate measurement of both gas and liquid CO2 RR products in flow cells.